Review paper Analgetic and sedative agents administered to the patients in life-threatening conditions - Machała, Waldemar; Rysz, Jacek; Gaszyński, Tomasz; Gaszyński, Wojciech (Archives of Medical Science, 2005)
Pharmacotherapy implemented to the patients who are in the life-threatening condition should be carried out in a quick and prepense way. The general condition of the patients in this state, after being administered strongly effecting drugs such as analgesics and sedatives may become not better but worse. In the following work the authors presented the modern approach and methods of administering analgesics and sedatives (including general intravenous anaesthetics) to the patients who sustained injuries as a result of a car accident. The authors presented opioids and non-steroid anti-inflammatory drugs, considering their administration prior to full access to the victim. They also discussed the risk connected with administration of strongly effecting drugs and indicated the interactions between administered substances.